Electromechanical behaviour of REBCO tape lap splices under transverse compressive loading. (3rd June 2016) - Grether, A; Scheuerlein, C; Ballarino, A; Bottura, L
Abstract: We have studied the influence of transverse compressive stress on the resistance and critical current ( I c ) of soldered REBCO tape lap splices. Internal contact resistances dominate the overall REBCO lap splice resistances. Application of transverse compressive stress up to 250 MPa during the resistance measurements does not alter the resistance and I c of the soldered REBCO splices that were studied. The resistance of unsoldered REBCO tape lap splices depends strongly on the contact pressure. At a transverse compressive stress of 100 MPa, to which Roebel cables are typically exposed in high field magnets, the crossover splice contact resistance is comparable to the internal tape resistances.